Pemerolehan Bahasa Anak Usia 2,6-5,0 Tahun Di PAUD Bakti Bunda Tabing Padang - Efrianto M.Pd (STKIP Pesisir Selatan, 2016)
Abstract This research aimed to describe the four things. The first, is the categories of words that had been acquire by children age 2,6-5,0 at PAUD Bakti Bunda Tabing Padang. The second is the kinds of meaning that had been acquire by children age 2,6-5,0 at PAUD Bakti Bunda Tabing Padang. The third is the semantic field that had been acquire by children age 2,6-5,0 at PAUD Bakti Bunda Tabing Padang. The last is the development stage of semantic acquisition of children age 2,6-5,0 at PAUD Bakti Bunda Tabing Padang This research was a qualitative research. It tried to understand the children age 2,6-5,0 language acquisition at PAUD Bakti Bunda Tabing Padang. The sources of data were the subject of research (the pupils) and the respondents (the teachers). The research instruments were the researcher it self and supported by data instrumentation. Ther method of data gathering was listening method. This method was used to listen the language acquisition by children age 2,6-5,0 at PAUD Bakti Bunda Tabing Padang. The validity technique of this research was the researchers pesverance. Data analysis was conducted by several steps based on the research purposes.The findings of research shown the pupils of PAUD Bakti Bunda Tabing Padang were, (1) the children were able to use verb, adjective, nominal, pronoun, number, adverb and action verb in base from as well as the derivative, (2) the children were able to understand and use the language containing lexical, grammatical, referential, non referential, denotative and word meaning, (3) most of children acquired the word in action semantic field, and (4) the children had tendency in semantic acquisition in semantic field stage.Keywords: Children Age 2,6-5,0 Language Acquisition